2002
DOI: 10.2527/2002.8071791x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of implant strategy on finished body weight of beef cattle

Abstract: We summarized experimental data to quantify the change in final BW due to a particular implant strategy when cattle are adjusted to the same final body composition. The database developed for this study included 13 implant trials involving a total of 13,640 animals (9,052 steers and 4,588 heifers). Fifteen different implant strategies were used among these trials, including no implant (control), single implants, and combinations of implants. Individual carcass data collected at slaughter were used to calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 9 publications
9
92
0
2
Order By: Relevance
“…Over the 75-d feeding period, use of GP technologies did not improve feedlot performance measures, which is in contrast to the plethora of literature that documents drastic improvements in these measures. When examining studies that utilize implant strategies that consist of a similar hormone dosage as the current study (200 mg trenbolone acetate/20 mg estradiol), heifer ADG and G:F can be increased by up to 50% and 31%, respectively (Herschler et al, 1995;Popp et al, 1997;Guiroy et al, 2002). In agreement with the current study, Garber et al (1990) found that implanting heifers with Synovex-H did not affect G:F; however, ADG was improved by the implant.…”
Section: Growth-promoting Technologies Effectssupporting
confidence: 79%
“…Over the 75-d feeding period, use of GP technologies did not improve feedlot performance measures, which is in contrast to the plethora of literature that documents drastic improvements in these measures. When examining studies that utilize implant strategies that consist of a similar hormone dosage as the current study (200 mg trenbolone acetate/20 mg estradiol), heifer ADG and G:F can be increased by up to 50% and 31%, respectively (Herschler et al, 1995;Popp et al, 1997;Guiroy et al, 2002). In agreement with the current study, Garber et al (1990) found that implanting heifers with Synovex-H did not affect G:F; however, ADG was improved by the implant.…”
Section: Growth-promoting Technologies Effectssupporting
confidence: 79%
“…Observa-se que, em animais castrados, a magnitude do aumento dos conteúdos corporais de gordura e, conseqüentemente, de energia, é maior, uma vez que animais castrados depositam, com mesmo peso vivo, mais gordura que animais inteiros. A menor deposição de gordura no corpo, seguida por maior concentração protéica do ganho de peso em animais inteiros, é explicada pela síntese e secreção dos hormônios androgênicos, substâncias esteróides com ação anabólica pronunciada no organismo animal (Guiroy et al, 2002). Como esses hormônios são sintetizados nas gônadas (testí-culos), animais castrados não apresentam o mesmo ímpeto anabólico dos animais inteiros e, conseqüente-mente, sintetizam menos proteína, sendo a energia disponível desviada para a síntese de gordura.Esse comportamento da composição corporal explica os maiores requerimentos de energia de bovinos castrados em relação aos inteiros.…”
Section: Resultsunclassified
“…The experiment was designed to harvest all finished cattle when FT was visually estimated to be 1.27 cm. However, because of the imprecision of the estimation, cattle were harvested at differing degrees of FT. To account for differences in performance caused by dissimilar management among treatments FT, HCW and marbling must be adjusted to a common harvest endpoint (Guiroy et al, 2002;Tedeschi et al, 2004). Cattle from this study were compared at similar harvest endpoint following the procedure described by Griffin et al (2007).…”
Section: Weaned Calf Managementmentioning
confidence: 99%